ANALISIS PENGARUH CASH RATIO, DEBT TO EQUITY RATIO, RETURN ON ASSET, FIRM SIZE, DAN EARNING PER SHARE TERHADAP DIVIDEND PAYOUT RATIO (Studi pada Perusahaan Manufaktur yang Go Public di BEI) - Rizky Dwiatmoko, 10.05.51.0069; Parmono Hadi, Teguh (Students Journal of Economic and Management, 2014)
This study was conducted to examine the effect of variable Cash Ratio, Debt to Equity Ratio (DER), Retun on Assets (ROA), Firm Size, and Earnings Per Share (EPS) of the Dividend Payout Ratio at manufacturing companies that went public in Indonesia Stock Exchange period 2009-2012. The population in this study is manufacturing companies listed in Indonesia Stock Exchange 2009-2012 period the number of 140 companies in 2009, 142 companies in 2010, 133 companies in 2011, and 142 companies in 2012 The sampling technique used was purposive sampling criteria: (1) manufacturing company that went public that publish their financial statements in a row during the years 2009-2012, and (2) companies that pay dividends at least once during the study period. Data obtained from the publication of Indonesian Capital Market Directory (ICMD 2013). Obtained a total sample of 29 companies in the year 2009, 28 companies in the year 2010, 27 companies in the year 2011, and 35 companies in the year 2012. Based on the analysis it can be concluded that: (1) Cash Ratio influence on Parliament. (2) Debt To Equity Ratio has no effect on the House of Representatives. (3) Return on Assets positive influence on Parliament. (4) Firm Size positive influence on Parliament. (5) Earning Per Share has no effect on the House of Representatives.Keywords: Cash Ratio, Debt to Equity Ratio, Retun On Asset, Firm Size, dan Earning Per Share dan Dividend Payout Ratio